1998
DOI: 10.1097/00007632-199810150-00010
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Health Outcome and Length of Hospital Stay in Lumbar Microdiscectomy

Abstract: Hospital length of stay for lumbar microdiscectomy can be decreased without adverse effect on short-term patient self-reported health status or satisfaction and with lower hospital charges. This model assesses the effect of efficient management of health care resources on patient-perceived quality and satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 10 publications
0
22
0
1
Order By: Relevance
“…Such differences may have different implications when analyzed from the perspective of the patient, surgeon, hospital, or insurance provider. Lorish et al 9 have suggested that, from the perspective of the insurance provider, the cost savings of a 1-day versus a 2-day hospitalization after lumbar discectomy is ~ $781. A prospective, randomized clinical trial has been proposed to specifically address the issue of costeffectiveness.…”
Section: Effect Of a Minimally Invasive Approach On Perioperative Outmentioning
confidence: 99%
“…Such differences may have different implications when analyzed from the perspective of the patient, surgeon, hospital, or insurance provider. Lorish et al 9 have suggested that, from the perspective of the insurance provider, the cost savings of a 1-day versus a 2-day hospitalization after lumbar discectomy is ~ $781. A prospective, randomized clinical trial has been proposed to specifically address the issue of costeffectiveness.…”
Section: Effect Of a Minimally Invasive Approach On Perioperative Outmentioning
confidence: 99%
“…This perspective allows us to see that the results are the product of the disease motivating the patient's admission, without influence of other factors such as co-morbidity and orthopedic morbidity, or, as expected from the preceding publications [26], age. There are several references about populations of other countries that use the SF-36 in the same way in patients with lumbar disease, i.e., standardizing by age and gender [12,35,39,53]; this is not so in Spain, where our study is the first to compare these four groups of diseases using the T scores of the SF-36.…”
Section: Discussionmentioning
confidence: 99%
“…In any case, when we adjust the results for age and gender (an adjustment not made in previous studies), statistically significant differences in quality of life begin to emerge in patients with lumbar disease as compared to the other groups [4,19,28,35,42].…”
Section: Discussionmentioning
confidence: 99%
“…Patients reporting improvement after surgery reached higher the PCS score and the MCS score. On the other hand, the fact of not taking analgesics has been connected only with the MCS [22,23]. The dependence appears interesting in that it is not the physical condition, yet the psychological one that is decisive for taking analgesics.…”
Section: Discussionmentioning
confidence: 99%